STUDI ANALISIS BERTAHANNYA METODE CERAMAH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM TINGKAT SMP/MTs - Novria Grahmayanuri; Muhammad Iqbal; Nora Adi Anna Harahap; Ika Maulida Thamimi; Efira Andiyani Batubara (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The lecture method continues to be used in the PAI learning process due to its widespread use in Indonesian education. The study employs a qualitative approach. Teachers of Islamic Religious Education from a variety of SMP/MTs schools located throughout the city of Medan served as the study's subjects. The subject of the study, on the other hand, is the persistence of the lecture method for comprehending Islamic Religious Education lessons as well as the reasons for its continued use. Techniques like observation, interviews, and documentation were used to collect data. The teacher's understanding of the situation and needs of the students is the reason that the lecture method is used to understand Islamic Religious Education lessons at the SMP/MTs level in Medan City. The lecture method is applied by combining other methods, the initial method of introducing a material, and inadequate school facilities are the teacher's choice to use the lecture method. The most unique reason is that the student's family has a broken home, so the teacher must provide material to the students using the lecture method. Questions and answers, group demonstrations, and presentations are all part of the teacher's process of surviving the lecture method. Combining the lecture method with other methods makes it more appealing to students.